Penggunaan Kata Tidak Baku dalam Penyampaian Konsep Geografi di Media Sosial : (Studi Kasus: Mahasiswa Pendidikan Geografi Universitas Negeri Medan) - Mira Susila Warni; Sri Muthia Hasan; Lili Tansliova (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The use of social media has become an important part of our lives, including in the development of geographic science. However, we often see that there are many uses of non-standard words in conveying geographic concepts on social media which can interfere with the effectiveness of conveying information and understanding geographic concepts. The aim of this research is to increase students' understanding of the importance of learning and understanding non-standard language terms in social media. This research uses quantitative research methods by distributing questionnaires to geography education students at Medan State University. The results of the research conducted show that geography education students have a positive view of the use of non-standard words on social media because they can increase students' understanding and interest in learning about geographic concepts.